BRONCHO- AND ANGIOPLASTY LOBECTOMY AS AN ALTERNATIVE TO PNEUMONECTOMY IN TREATMENT OF NON-SMALL-CELL LUNG CANCER - A. V. Reshetov; A. V. Elkin; G. V. Nikolaev; S. S. Stepanov (Вестник хирургии имени И.И. Грекова)
The objective of the study is to substantiate the applying of broncho- and angioplasty lobectomy as an alternative to pneumonectomy in NSCLC.Material and methods. The results of treatment of two comparable groups of patients with NSCLC were presented. In one group, patients underwent broncho- or angioplasty lobectomies (group A), in another – pneumonectomy (group B). The number of complications, overall and disease-free survival in both groups, as well as the factors affected the results were analyzed.Results. The number of postoperative complications in group A and group B was 12.5 % and 15.6 %, respectively. The median of disease-free survival and overall survival in both groups did not differ meaningfully, consisting of 20 months and 48 months in group A, and 19 months and 25 months in group B (p=0.91) and (p=0.97). The results of treatment were meaningfully affected only by the stage of the disease (p=0.017) and multidisciplinary treatment (p=0.007), including chemotherapy and radiation therapy.Conclusions. Performing of broncho- and angioplasty lobectomies can be justified as an alternative to lung removal in NSCLC within the multidisciplinary treatment.